PENGARUH EXPERIENTIAL MAREKTING DAN KEPUASAN TERHADAP LOYALITAS PELANGGAN PADA TIJILI HOTEL SEMINYAK - NI PUTU ASTARI KIRANA; IDA BAGUS SANJAYA; KASIANI KASIANI; COKORDA GEDE PUTRA YUDISTIRA (GANEC SWARA, 2021)
The development of knowledge and communication technology, as well as increased competitiveness, make the concept of experiential marketing offered as a strategy in marketing. This concept supports strategically to increase customers and maintain customer loyalty. One way that can be done to increase customer loyalty is to give satisfaction to the customers. Customer satisfaction is the key to the success of a business. The purpose of this study is to determine and analyze the influence of experiential marketing and customer satisfaction on customer loyalty at Tijili Hotel Seminyak. Data was collected through questionnaire method. The sampling technique is the purposive sampling technique with the number of samples is 118 respondents who have stayed at least 2 times at Tijili Hotel Seminyak. This study uses multiple linear regression analysis technique. The results showed the experiential marketing variable has a positive and significant effect on customer loyalty with a significance of 0,000 and a regression coefficient of 0.278. Customer satisfaction also has a positive and significant effect on customer loyalty with a significance of 0,000 and a regression coefficient value of 0.494. Simultaneously, experiential marketing and satisfaction variables have a positive and significant effect on customer loyalty of Tijili Hotel Seminyak with the acquisition of a coefficient of determination of 78.1%, while the remaining 21.9% is influenced by other factors not examined.